PENYEBARAN PRODUK HUKUM DAERAH MELALUI JARINGAN DOKUMENTASI DAN INFORMASI HUKUM DI INDONESIA - Dewi, Hesty; Helmi, Helmi; Syamsir, Syamsir (Ensiklopedia of Journal, 2024)
Based on Presidential Decree Number 33 of 2012, the government established a forum called the Legal Documentation and Information Network (JDIH), where the National Legal Development Agency of the Ministry of Law and Human Rights is the Center for the National Documentation and Information Network (JDIHN). As an implementation of Presidential Decree Number 33 of 2012, the National Legal Development Agency of the Ministry of Law and Human Rights issued Regulation of the Minister of Law and Human Rights Number 2 of 2013 which was subsequently amended by Regulation of the Minister of Law and Human Rights Number 8 of 2019 concerning Standardization of Technical Management of Legal Documentation and Information. Regulations regarding JDIH are further regulated in Minister of Home Affairs Regulation Number 2 of 2014 concerning Management of the Legal Documentation and Information Network of the Ministry of Home Affairs and Regional Government. Based on the explanation above, it appears that there are 2 (two) implementing regulations for Presidential Decree Number 33 of 2012, namely Minister of Law and Human Rights Regulation Number 8 of 2019 concerning Standardization of Technical Management of Legal Documentation and Information and Minister of Home Affairs Regulation Number 2 of 2014 concerning Network Management Documentation and Legal Information of the Ministry of Home Affairs and Regional Government. The existence of more than one implementing regulation creates a conflict of norms, especially in the implementation of regional legislative programs, which of course will give rise to multiple interpretations for regional governments, which regulations must be followed or prioritized in implementing information disclosure, especially information about regional legislative programs.Keywords: Regional Legal Products, Network, Documentation, Information, Law